Role of Titanium-Reinforced Platelet-Rich Fibrin in Periodontal Tissue Regeneration-A Systematic Review - Manchala, Bhavya; Teju, Anurag; Pasupuleti, Mohan Kumar; Penmetsa, Gautami S; Gottumukkala, Sruthima; Lakshmi, Venkata (UI Scholars Hub, 2024)
Objective: The objective of the study is to demonstrate the efficacy of Titanium reinforced platelet-rich fibrin (T-PRF) as the sole biomaterial amongst the biologics in periodontal regeneration of both soft and hard tissues. Methods: A PUBMED database search is conducted from August 2013 to August 2023. Only original articles, including Randomized controlled clinical trials, cross-sectional studies, prospective studies, and case-control studies, were included. The studies will be analyzed regarding the outcome of the association between T-PRF and periodontal regeneration of both hard and soft tissue. Results: From 35 articles identified, 8 RCTs were included. The use of T-PRF statistically significantly reduced PD and improved CAL and Radiographic bone fill. On soft tissue regeneration, better results in terms of PPD, CAL, RGML, Recession Depth, and an increase in thickness of attached gingiva are observed. Conclusion: The use of T-PRF significantly improved clinical outcomes in hard tissue regeneration and periodontal parameters, including the soft tissue outcomes in root coverage procedures.